NYAI MUNAWWARAH'S WOMEN LEADERSHIP IN AR-RASYID ISLAMIC ELEMENTARY SCHOOL TO SUSTAIN LEARNING EXCELLENT SERVICE - Shulhan, Shulhan (Universitas Islam Negeri Kiai Ageng Muhammad Besari Ponorogo, 2025)
The research aimed to portray women's leadership in education in Madura through a case study of Nyai Munawwarah's leadership in Madrasah Ibtidaiyah Ar-Rasyid, Sumenep. Using a qualitative approach, data were collected through observation, interviews and documentation, then analysed thematically. The results showed that Nyai Munawwarah utilised social capital such as community networks, norms of reciprocity and trust to sustain the madrasah after the death of the founder. The main challenges include financial limitations, undisciplined management of certified teachers, and value conflicts between generations of teachers. Her leadership strategies include: (1) building teachers' collective awareness to have a sense of responsibility towards the madrasah through motivation, dialog or communication, and exemplification; and (2) improving the quality of education services by enforcing the discipline of certified teachers and regenerating leadership. Nyai Munawwarah's leadership reflects a servant leadership model that prioritises personal sacrifice and a humanist approach, although it depends on individual resilience. The research concludes that while women's leadership can drive community-based education, institutional sustainability requires structural support such as transparent evaluation systems, performance-based incentives and participatory governance. The implication is affirmative policies needed to strengthen the role of women in the leadership of Islamic education while overcoming patriarchal bias.